2015
DOI: 10.1002/ana.24428
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant astrocytes impair vascular reactivity in Huntington disease

Abstract: Our findings suggest that the inflammation-prone HD astrocytes provide less pericyte coverage by promoting angiogenesis and reducing the number of pericytes and that these changes can explain the inferior VR in HD mice. The resultant impaired VR might hinder cerebral hemodynamics and increase brain atrophy during HD progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 45 publications
(127 reference statements)
0
67
1
1
Order By: Relevance
“…The association between astrocytes and BV after retinal injury could have important physiological consequences. Indeed, in an animal model of Huntington’s disease astrocytes promote angiogenesis and reduce the number of pericytes associated with BV by an increased production of vascular endotheial growth factor (A) and IkB (Hsiao et al, 2015)…”
Section: Resultsmentioning
confidence: 99%
“…The association between astrocytes and BV after retinal injury could have important physiological consequences. Indeed, in an animal model of Huntington’s disease astrocytes promote angiogenesis and reduce the number of pericytes associated with BV by an increased production of vascular endotheial growth factor (A) and IkB (Hsiao et al, 2015)…”
Section: Resultsmentioning
confidence: 99%
“…Reactive astrogliosis may contribute to pericyte demise, causing a reduced pericyte overlay of cerebral blood vessels and worsened vascular reactivity. This, in turn, may modify the normal cerebral circulation and thus contribute to the disease progression (Hsiao et al ., 2015). …”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Besides the most commonly functional abnormalities described in HD pathology, it has been recently reported that the cerebral vascular system is also significantly disrupted in the disease34.…”
mentioning
confidence: 99%